PENGARUHKUALITAS PRODUK, PERSEPSI HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA DISTRO HOUSE OF SMITH SEMARANG - Cucun Fery Tri Arbi, 11.05.51.0110 (Students Journal of Economic and Management, 2016)
This study was done toanalyze the effects of product quality, price perception and promotion to purchase decisions in distroHouse Of SmithSemarang. The population in this study is that consumers who make purchases at the distroHouse Of SmithSemarang. Sampling method used in this study was